Pembinaan Public Speaking Pada Lapas Anak Kelas IIB Kota Batam - Ageng Rara Cindoswari; Sholihul Abidin (Universitas Garut, 2022)
Abstract The limited resources of teaching staff and coaching materials are problems that arise in the coaching process that occurs in class IIB children's prisons in Batam City. On the other hand, the ability to speak in public becomes a sufficient skill and expertise to generate income. Some of the professions that are in great demand in the world of work include professions related to the ability to speak in public, for example work as a public relations officer, marketing officer, journalist, presenter, so that coaching related to public speaking for the inmates of the IIB Children's Prison in Batam City is necessary. conducted. The purpose of this service is to provide public speaking coaching for class IIB prison children. The method of devotion carried out through coaching is carried out 3 times face-to-face where at each meeting participants will be provided with skills in public speaking, namely about the practice of knowledge and writing speeches. The results of this activity are (1) The development of public speaking at the children's prison in Batam went smoothly, which was greeted with high enthusiasm and motivation to learn, (2) The material presented in the coaching is in accordance with the needs of the participants as skill capital when they are free later, (3) The inmates' ability to speak in public is quite good after attending the coaching meeting. Key words: Public speaking; talk; coaching; child wipes. Â Abstrak Keterbatasan sumber daya tenaga pengajar dan materi pembinaan menjadi persoalan yang menonjol pada proses pembinaan terjadi pada lapas anak kelas IIB di Kota Batam. Di sisi lain, kemampuan berbicara di depan umum dewasa ini menjadi keterampilan dan keahlian yang cukup menjanjikan untuk menghasilkan pendapatan. Beberapa profesi yang sangat diminati dalam dunia kerja diantaranya adalah profesi yang berkaitan dengan kemampuan berbicara di depan umum contoh saja pekerjaan sebagai humas, marketing officer, jurnalis, presenter, sehingga pembinaan terkait dengan public speaking pada warga binaan lapas anak IIB di Kota Batam perlu dilakukan. Tujuan pengabdian ini adalah untuk memberikan pembinaan public speaking pada anak lapas kelas IIB. Metode pengabdian yang dilakukan melalui pembinaan dilakukan sebanyak 3 kali tatap muka di mana pada masingmasing pertemuan peserta akan dibekali pengetahuan dan keterampilan dalam public speaking yakni seputar praktek pidato dan penulisan naskah berpidato. Hasil kegiatan ini adalah (1) Pembinaan public speaking pada lapas anak di kota batam berjalan dengan lancar, dimana disambut dengan antusiasme dan motivasi belajar yang tinggi, (2) Materi yang disajikan pada pembinaan sesuai dengan kebutuhan peserta sebagai modal keterampilan ketika bebas kelak, (3) Kemampuan berbicara didepan umum yang dimiliki oleh warga binaan cukup baik setelah mengikuti serangkaian pertemuan pembinaan.Kata-kata kunci: Public speaking; pidato; pembinaan; lapas anak.Â